Анализ неопределенностей причин тяжелых аварий на АЭС Fukushima-Daiichi - Васильченко, С.В.; Волошина, С.Л.; Габлая, Т.В.; Кочнева, В.Ю.; Скалозубов, К.В. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2013)
Проводится анализ неопределенностей причин тяжелых аварий на АЭС Fukushima-Daiichi, связанных с
состоянием активной зоны и корпусов реакторов, природой и механизмами возникших парогазовых взрывов,
эффективностью действий персонала по снижению давления в контайнменте и охлаждению поврежденного
топлива. Наведено аналіз невизначеностей причин важких аварій на АЕС Фукусіма-Daiichi, пов'язаних зі станом
активної зони і корпусів реакторів, з природою та механізмами, що виникли в результаті парогазових вибухів, з
ефективністю дій персоналу зі зниження тиску в контайнменті та охолодження пошкодженого палива. The paper analyses uncertainty of causes of severe accidents at Fukushima-Daiichi relating to a state of a reactor
core and vessels, the nature and mechanisms of steam-gas explosions, efficiency of stuff’s actions to decrease pressure
in containment and to cool the damaged fuel. It is shown that the main uncertainties are: the state of uncertainty in
the core and the reactor pressure during the development of accidents at power units № 1 - 3 determines the possibility
of different scenarios, the uncertainty of the nature and mechanisms arising steam explosions uncertainty effectiveness
of personnel to reduce the pressure in the containment vessel and the cooling of the molten / damaged fuel.